THE REPRESENTATION OF SELECTED UZBEK FOLK LEXEMES IN EXPLANATORY DICTIONARIES - Mexlieva Dilnoza Usmonovna (International Journal of Literature and Language Studies, 2026)
This article examines the representation of selected Uzbek folk lexemes in explanatory dictionaries from a lexicographic and historical-semantic perspective. Special attention is paid to the lexeme alp, which occupies an important place in the linguistic and cultural heritage of the Turkic peoples. The study analyzes the interpretation of this lexeme in Old Turkic, Chagatai, explanatory, etymological, and electronic dictionaries and identifies the main directions of its semantic development. Comparative analysis shows that the core seme of heroism has remained stable from the eleventh century to the present, while its lexicographic interpretation has varied depending on the type and purpose of the dictionary. The article highlights the relationship between semantic stability and lexicographic description and demonstrates how historical, cultural, and cognitive factors influence dictionary definitions. The findings reveal that the lexeme alp functions not only as a linguistic unit but also as a cultural concept reflecting bravery, courage, social prestige, and moral excellence. The scientific novelty of the study lies in the identification of a four-component model consisting of definition, explanation, example, and etymological note, which enables a unified comparison of dictionary entries across different historical periods. The results contribute to the fields of historical lexicology, lexicography, and Turkic studies and provide a basis for further research on the representation of folk lexicon in Uzbek dictionaries.